Mechanized tree planting in Finland and improving its productivity - Laine, Tiina (The Finnish Society of Forest Science, University of Helsinki, University of Eastern Finland, 2017)
The demand for mechanized tree planting is expected to increase in the future. This dissertation assessed mechanized tree planting in Finland and suggests ways to improve its current productivity. The work on which this thesis is based was described in five peer-reviewed articles (I–V) addressing four specific research questions (SQs) that focus on productivity and cost-competitiveness, automation, capacity utilization, and the quality of planting work. While productivity of mechanized planting is higher than manual methods, it is not yet cost-competitive. However, increasing efficiency by skilled operators and worksite selection make it possible for mechanized planting costs to remain lower than those of excavator spot mounding followed by manual planting. Increasing productivity and reducing operating costs are possible with an effective automatic seedling feeding system, although the Risutec APC is not yet sufficiently developed to reach that goal. Planting machine capacity is underutilized and could be utilized more effective to enhance productivity and cost-efficiency. Technical availability of planting machines in Finland is good, and the quality of mechanized planting work is high. Optimization and integration of the entire mechanized planting chain from the nursery to outplanting is important to minimize total cost. In summary, for mechanized planting to be effective the following criteria must be satisfied: machine reliability; highly-skilled machine operator; suitable worksite; seedling quality, availability, and supply to worksite. In the future, it is important to continue developing new and existing machines to enhance productivity, e.g., by continuously working planting machines.
Keywords: planting machine; koneellinen metsänistutus; koneellinen istutus; koneellistaminen; koneistuminen; metsänhoito; metsänuudistus; taimet; istutuskoneet; mechanization; silviculture; regeneration; seedlings